Analisis Transformasi Generatif Pada Nazam Kitab Al-Jawhar Al-Maknun - Sayidina Ali; Wardani, Yani’ah; Buana, Cahya (Universitas Negeri Jakarta, 2025)
This study aims to identify the forms of vocabulary units and distinguish between the deep structure and surface structure of naẓm al-Jawhar al-Maknūn by ʿAbd al-Raḥmān al-Akhdarī. The method used is descriptive, employing a theoretical linguistic approach. The analysis is based on Noam Chomsky’s theory of transformational-generative grammar to examine the syntactic structure of naẓm al-Jawhar al-Maknūn. The results of this study show that transformational-generative grammar can be applied to various forms of language. The conclusions are as follows: (1) the structure of naẓm al-Jawhar al-Maknūn is dominated by jumlah ismīyah (sentences that begin with a noun), with only a few jumlah fi‘līyah (sentences that begin with a verb); (2) structural transformations in the deep structure include deletions and replacements, while in the surface structure they involve mutations and additions to the sentence structure. Thus, this study contributes to the application of transformational-generative linguistic theory to Arabic grammar in the form of naẓm, whereas previous research has generally focused only on rhetorical aspects (balāghah), Arabic language teaching materials, and the grammar of the Qur’an.